Diet, Physical Activity, Weight Status, and Culture in a Sample of Children from the Developing World - Pamela S. Gaskin; Pamela Lai; Devon Guy; JaDon Knight; Maria Jackson; Anders L. Nielsen (Journal of Nutrition and Metabolism)
Objective. Barbados, a small developing state at the end of the nutrition transition, faces an obesity epidemic. Although there is hope of stemming the epidemic in childhood, no descriptions of children's dietary and physical activity (PA) patterns are available for planning purposes. We describe the food and activity preferences and adult encouragement of active and sedentary behaviors for children 9–11 years in relation to weight status and the cultural context. Design. We used data from a pilot study preceding a large-scale ongoing study on the local drivers of the obesity epidemic among preadolescent children. PA, sedentary activity, and dietary intakes were assessed from recalls. Weight and height were measured. Setting. Barbados. Subjects. Sixty-two (62), 9–11-year-old school children. Results. Sugar-sweetened beverages provided 21% of energy consumed. Energy intake significantly explained BMI. Parents selected significantly more of children’s sedentary activities and encouraged mostly homework and chores (59%). Children’s self-selected school-based activity was significantly related to BMI. Conclusions. Childhood obesity prevention recommendations and research should focus on culture-specific practices that promote acquired taste for excess sugar and parent-child interactions regarding PA. Child influenced by school-based activity intervention may an important area for preventive intervention research.